Giant Nevus Lipomatosus Cutaneous Superficialis with Cerebriform Surfaces on the Back and Sacral Region: A Case Report - Li S; Xiao Y; Wang H; Liu Z (Dove Medical Press, 2022)
Shuo Li,1,* Yiding Xiao,1,* He Wang,2 Zhifei Liu1 1Department of Plastic Surgery, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100730, People's Republic of China; 2Department of Neurological Surgery, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100730, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhifei Liu, Email zhfeliuliuchong@163.comAbstract: Nevus lipomatosus cutaneous superficialis (NLCS) is a rare hamartoma of adipose tissue characterized by the ectopic build-up of adipose tissue among collagen bundles and proliferation of ectopic adipocytes in the dermis, which leads to an absence of connection to the subcutaneous tissue. Giant NLCS (over 15 × 15 cm) is even rarer. So far, the largest NLCS mass in the literature was a giant lesion measuring 50 × 50 cm on the sacral area reported in 2014. Herein, we report a case of an even larger NLCS lesion with a size of 106 × 30 cm on the back and sacral regions. These lesions had been left untreated and had grown from small yellowish papules and nodules to giant multilocular pedunculated masses with cerebriform surfaces over 24 years. To the best of our knowledge, the NLCS lesion presented here is the largest reported. The report aimed to increase clinicians' awareness of this rare and easily misdiagnosed disease. Furthermore, physicians should be mindful that early recognition and appropriate treatment are essential for NLCS patients, and lesions of NLCS can coalesce into unimaginable huge masses if left untreated resulting in more significant therapeutic challenges.Keywords: nevus lipomatosus cutaneous superficialis, giant mass, early recognition, ectopic adipocytes, surgical resection and skin graft